INSTITUTIONAL CREDIT AND ORGANIC FARMING: EVIDENCE FROM SELECT ORGANIC CROPS IN SIKKIM - Sharma, Keshar Prasad; Devi, Mridula (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research examines how institutional agricultural financing impacts the production of important organic crops such as rice, maize, wheat, buckwheat, finger millet, and barley in Sikkim, India's first entirely organic state. Analysis of survey data from 400 farmers shows that obtaining formal credit greatly enhances agricultural productivity. Additional influencing factors consist of land ownership, agricultural experience, and involvement in training and extension programs, all of which enhance farm productivity. In contrast, the nuclear family structure has a negative correlation with output, highlighting the benefits of shared labor and resources found in joint families. Elements like gender, level of education, and closeness to financial institutions demonstrated minimal or no direct impact on productivity. The research highlights the essential importance of institutional finance and capacity-building programs in improving organic farming results and indicates that specific policy measures can promote sustainable agricultural growth in the area.